2020
DOI: 10.1002/jlb.1a1119-223r
|View full text |Cite
|
Sign up to set email alerts
|

Themacrophage-expressed gene(mpeg)1identifies a subpopulation of B cells in the adult zebrafish

Abstract: The mononuclear phagocytic system consists of many cells, in particular macrophages, scattered throughout the body. However, there is increasing evidence for the heterogeneity of tissue‐resident macrophages, leading to a pressing need for new tools to discriminate mononuclear phagocytic system subsets from other hematopoietic lineages. Macrophage‐expressed gene (Mpeg)1.1 is an evolutionary conserved gene encoding perforin‐2, a pore‐forming protein associated with host defense against pathogens. Zebrafish mpeg1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 55 publications
(124 reference statements)
1
30
0
Order By: Relevance
“…This increase in morphologically activated 4C4+ microglia spanned the time period between 72 hpl and 10 dpl, dropping back down to baseline levels by 14 dpl, when the newly born photoreceptors are maturing. At the transcript level, we analyzed mpeg1.1 expression, a known transcriptional marker of microglia and macrophages in zebrafish ( Ferrero et al, 2020 ). The rise in mpeg1.1 expression immediately preceded the peak in 4C4+ microglia localized to the debris field, and then steadily dropped as microglia cleared the area ( Figures 4L–V ).…”
Section: Resultsmentioning
confidence: 99%
“…This increase in morphologically activated 4C4+ microglia spanned the time period between 72 hpl and 10 dpl, dropping back down to baseline levels by 14 dpl, when the newly born photoreceptors are maturing. At the transcript level, we analyzed mpeg1.1 expression, a known transcriptional marker of microglia and macrophages in zebrafish ( Ferrero et al, 2020 ). The rise in mpeg1.1 expression immediately preceded the peak in 4C4+ microglia localized to the debris field, and then steadily dropped as microglia cleared the area ( Figures 4L–V ).…”
Section: Resultsmentioning
confidence: 99%
“…Adult zebrafish also possess populations of B cells (Page et al 2013) and natural killer-like cells (Carmona et al 2017), and recent studies demonstrate that a proportion of these populations are labelled by mpeg1.1 transgenics (Moyse and Richardson 2020;Ferrero et al 2020). Indeed, we have shown that these mpeg1.1 expressing lymphocytes respond to cardiac cryoinjury in a different temporal manner to mpeg1.1+ macrophages suggesting that they could play a role in repair or regeneration responses (Moyse and Richardson 2020).…”
Section: Lymphocytesmentioning
confidence: 73%
“…However, future work is necessary to further delineate the macrophage subsets that are responsible for these processes in zebrafish. Moreover, the recent finding that mpeg1.1, which has been ubiquitously used to label macrophages in zebrafish, is also expressed in a sub-population of B-lymphocytes and natural killer-like cells in adult zebrafish (Moyse and Richardson 2020;Ferrero et al 2020) demonstrates the need to expand and diversify macrophage markers. Macrophage phenotype and activation states are emerging as key regulators of these opposing processes (Bevan et al 2020), yet as the importance of the immune response in repair and regeneration becomes clear, the need to fully understand the roles of immune cells in these processes is ever greater.…”
Section: Macrophagesmentioning
confidence: 99%
“…As the definitive markers for B1a lymphocytes in zebrafish are elusive, other model organism like mice might be useful for our understanding Pdcd11-positive cells in the future. A recent report in studying the mpeg1.1:GFP reporter line, it found that beside macrophages, a subpopulation of B-lymphocytes is marked by mpeg1.1 reporters in most adult zebrafish organs, with highly expressed cd79a , ighm , and ighd [ 51 ]. This would also be helpful for our future examination of this transgenic line in study the property of Pdcd11-positive cells.…”
Section: Discussionmentioning
confidence: 99%